2013
DOI: 10.1039/c2tc00010e
|View full text |Cite
|
Sign up to set email alerts
|

Low operation voltage macromolecular composite memory assisted by graphene nanoflakes

Abstract: The trend towards simple and low-cost processing is one of the most important for macromolecular memory development. Here, bistable memory devices using a solution-processable active material, a mixture of graphene nanoflakes (GNFs) and insulating poly(vinyl alcohol) (PVA), are investigated, which serve as the first example for the direct integration of as-prepared nanoscale graphene into macromolecular memory devices through a one-step low-temperature processing method. Bistable electrical switching behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 56 publications
(64 reference statements)
1
43
0
Order By: Relevance
“…8) SCLC. The transport mechanism was in agreement with that reported by Ooi et al and Lai et al [34,35].…”
Section: Resultssupporting
confidence: 88%
“…8) SCLC. The transport mechanism was in agreement with that reported by Ooi et al and Lai et al [34,35].…”
Section: Resultssupporting
confidence: 88%
“…[21][22][23] It was also reported that the self-assembled structure as a template could direct the following lateral growth of the chain-folded lamella into different morphologies. [24][25][26][27] For instance, Varga prepared PP samples with spherulite, fibrous, dendric morphology by adjusting the melting temperature and concentration of the nucleating agent. 6 Dong indicated effect of final heating temperature on dissolution of b-nucleating agent and the following supermolecular structure of PP.…”
Section: Introductionmentioning
confidence: 99%
“…To gain insight into the electrical switching effects in the ITO/GO-PPy/Al device, the I-V data were analyzed by using different conduction models which included Ohmic contact, Fowler-Nordheim (F-N) tunneling, space charge limited conduction and thermionic emission limited conduction [1,25,41]. The results show that the OFF-state can be well described by the space charge limited conduction (SCLC) model, which is defined as [25]:…”
Section: The Resistive Switching Memory Propertiesmentioning
confidence: 99%
“…The low OFF-state current implies that the GO-PPy film owns a plenty of electron trap. The Ohmic model describes a linear relationship between the current and the applied voltage [1]:…”
Section: The Resistive Switching Memory Propertiesmentioning
confidence: 99%
See 1 more Smart Citation